Perspectives on the Extension and Diversification of Basil (Ocimum basilicum L.) Assortment by Exploiting Genetic Resources Conserved at The Plant Genetic Resources Bank of Buzău - Costel VÎNĂTORU; Bianca MUȘAT; Camelia BRATU; Geanina NEGOȘANU; Matilda POPESCU; Adrian PETICILĂ (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Horticulture, 2022)
The present study aims to evaluate the diversification of the current indigenous assortment of the genus Ocimum by obtaining new distinct genotypes with superior quality, following classical intraspecific hybridization and determination of their chemical composition. The germplasm collection contains 63 genotypes of which 27 are genetic stable. Among the stable genotypes, 4 genitors were studied as breeding material. The breeding procedures used were classical hybridization, negative mass selection and segregation. Laboratory analyses were also carried out in terms of chemical composition description. In the present research work, as a result of intraspecific hybridization, 4 new genotypes were obtained to enrich the local assortment of aromatic and medicinal plants of the genus Ocimum in Romania. The new morphotypes obtained have distinct characteristics and superior qualities.